Proceedings of the 22nd ACM International Conference on Information &Amp; Knowledge Management 2013
DOI: 10.1145/2505515.2505602
|View full text |Cite
|
Sign up to set email alerts
|

Identifying salient entities in web pages

Abstract: We propose a system that determines the salience of entities within web documents. Many recent advances in commercial search engines leverage the identification of entities in web pages. However, for many pages, only a small subset of entities are central to the document, which can lead to degraded relevance for entity triggered experiences. We address this problem by devising a system that scores each entity on a web page according to its centrality to the page content. We propose salience classification func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 35 publications
3
53
0
Order By: Relevance
“…The two other sources of semantic features are used as a point of comparison to the DSSM. One is a generative semantic model (Joint Transition Topic model, or JTT) (Gamon et al 2013). JTT is an LDA-style model (Blei et al 2003) that is trained jointly on source and target documents linked by browsing transitions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two other sources of semantic features are used as a point of comparison to the DSSM. One is a generative semantic model (Joint Transition Topic model, or JTT) (Gamon et al 2013). JTT is an LDA-style model (Blei et al 2003) that is trained jointly on source and target documents linked by browsing transitions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the notion of relevance as described in Section 1, related to interestingness is also the notion of salience (also called aboutness) (Gamon et al 2013;2014;Parajpe 2009;Yih et al 2006). Salience is the centrality of a term to the content of a document.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested the use of centering constructs to keep track of the key entities, which change with discourse. Document-level importance of entities (which include events) was explored by Gamon et al (2013). The authors use the term salience to denote entity importance and graded entities into 3 categories -most salient, less salient, not salient.…”
Section: Related Workmentioning
confidence: 99%
“…Information need expression: If an information need is detected, the query is constructed from the page's relevant entities. The task of extracting relevant entities is somewhat similar to extracting salient entities [1], but opposed to salience or aboutness, relevance incorporates the user's interests. The relevant terms are determined by a named entity recognizer, using an adapted ranking mechanism based on the relatedness of the candidate entities to interest topics in the user profile.…”
Section: Page Levelmentioning
confidence: 99%